Factors Affecting Time Performance of Tertiary Education Trust Fund Construction Projects in North-East, Nigeria - Mukhtar, M. M.; Abdussalam, D.; Mustapha, M. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Higher education institutions in Nigeria faced with the challenges of inadequate funding for the provision of facilities and rehabilitation of decaying ones. To address this issue, the Tertiary Education Trust Fund (TETfund) was established. However, it has been reported that, there are poor time performance of TETFund projects in tertiary institutions in Nigeria. This study was conducted to determine factors affecting time performance of Tertiary Education Trust Fund construction projects in north-east, Nigeria. Thirty-two (32) factors causing delay in construction projects were identified from the literature review. Data collection was carried out by means of survey questionnaire. One hundred and thirty-six questionnaires (136) were shared among construction professionals comprising of clients, contractors and consultants, 112 were returned completed representing 82% response rate. The data collected were analysed by means of frequency, severity index and Spearman’s rank correlation. The results obtained revealed that, the most common delay factor in TETFund construction projects according to the three categories of the respondents is late procurement of materials. Similarly, there is consensus among the three categories of the respondents that type of project bidding and award is one of the most severe delay factors in TETFund projects. Clients and consultants pointed out that, factors with high impacts on time performance include ineffective planning and scheduling of project by contractor, poor site management and supervision by contractor, and shortage of qualified workers. Whereas, based on contractors’ views, delay in progress payments by client has the highest impact. The study recommended that adequate planning and scheduling for all activities of project should be done by contractors at an appropriate time. The findings of this study can assist TETFund construction project team members to understanding factors that can significantly affect timely delivery of their projects.